Effect of Saponins from Chenopodium quinoa Willd. on Methane Production, Short Chain Fatty Acids and Digestibility in vitro Ruminal Fermentation - Alegría Arnedo, Maria Cecilia (2024)
The objective of this study was to assess the effects of saponins derived from Chenopodium quinoa by-products on methane (CH4) production in a ruminal fermentation system under in vitro conditions. Additionally, the study included the analysis of short-chain fatty acids (SCFAs) and true dry matter digestibility (TDMD). The saponin extracts obtained from three quinoa varieties were Altiplano (AS), Quillahuaman (QS), and Salcedo (SS), and were tested at six different doses (0, 0.2, 0.4, 0.6, 0.8, and 1.0mg/mL) each. Rumen fluid was obtained from two fistulated Junín breed sheep, with alfalfa hay (AH) and a 1:1 mixture of maize and bran (MB) was used as basal substrates. The data were processed in a completely randomized design and replicated three times. The CH4 per dry matter (mL/g DM), after 24h of incubation significantly decreased, acetate molar concentration decreased (p<0.05) with AS (3.6%) and QS (6.4%), propionate values increased (P<0.05) to 14.4% (AS), 15.7% (QS), and 15.5% (SS), the acetate-to-propionate ratio decreased (P<0.05) across all saponins treatments compared to the control and irrespective the substrates. The CH4 to TDMD ratio decreased (P<0.05) with all saponins. Methane inhibition (mL CH4/100mgTDMD) was higher by up 25.7% in the presence of AS, followed by QS at 18.7% and SS at 14.6%. The results indicate that saponins extracted from quinoa possess significant potential as feed additives for ruminants. Their application could contribute to the reduction of methane production, which would be advantageous for both livestock efficiency and environmental sustainability.